Penggunaan tepung daun kedondong laut beda komposisi terhadap pertumbuhan ikan Nila (Oreochromis niloticus) - Pasiali, Andris; Lumenta, Cyska; Kusen, Diane J. (Universitas Sam Ratulangi, 2019)
The aim of the study was to determine the effect of different compositions of kedondong laut leaf flour in feed formulations on absolute growth, daily growth, relative growth, feed efficiency, food conversion ratio. The test animals used were Nile tilapia with a size of 3-5cm in length and weigh between 1.3 - 2 g. Â Fish were stocked in nets measuring 50x50x50 cm3 with a density of 10 fish each. Â Fish were obtained from the Tatelu Aquaculture Fisheries Center, Dimembe District, North Minasaha Regency. The study was conducted by an experimental method using a complete randomized design (CRD). Â The treatments consisted of A without addition of kedondong laut leaves flour, Treatment B with addition of 10% kedondong laut leaf flour, Treatment C with addition of 20% kedondong laut leaf flour, Treatment D with addition of 30% kedondong laut leaf flour. The results of the experiment showed that treatment B was the best where absolute growth (23%), relative growth (287.3%), daily growth (3.93%), feeding efficiency (95.83 %) and food conversion ratio (1,044). Water quality during the experiment was in a reasonable range where the water temperature during experiment was 26oC, pH 7-8